1983
DOI: 10.1176/ajp.140.9.1159
|View full text |Cite
|
Sign up to set email alerts
|

Depression, delusions, and suicide

Abstract: A retrospective analysis of all the suicides at the New York State Psychiatric Institute over a 25-year period was carried out. The authors retrospectively assigned diagnoses according to Research Diagnostic Criteria and DSM-III and found that among the patients who committed suicide there were 14 with unipolar endogenous depression. Of those 14 patients, 10 were considered delusional or probably delusional. In comparison, a control group of similarly diagnosed depressed patients taken from the same institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(25 citation statements)
references
References 18 publications
4
21
0
Order By: Relevance
“…Botswick et al 14 also reported that impulsivity, aggression and psychosis increased in attempters. Roose et al 15 concluded that delusional, depressed patients were five times more likely to commit suicide than non-delusional ones.…”
Section: Discussionmentioning
confidence: 99%
“…Botswick et al 14 also reported that impulsivity, aggression and psychosis increased in attempters. Roose et al 15 concluded that delusional, depressed patients were five times more likely to commit suicide than non-delusional ones.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for selecting these 16 variables was based on previous findings that reported the following risk factors for suicide attempts or suicide, i.e., younger age [ 21 , 22 ], female gender [ 21 , 22 ], low education level [ 21 , 22 ], unmarried status [ 21 , 22 ], unemployment [ 22 , 23 ], living alone [ 24 , 25 ], past suicidal behaviors [ 24 , 26 ], family history of psychiatric disorders [ 27 , 28 ] and suicide deaths [ 27 ], bipolarity [ 29 , 30 ], agitation during a depressive episode [ 31 , 32 ], psychotic features [ 33 , 34 ], physical diseases [ 35 , 36 ], alcohol abuse [ 24 , 37 ], cluster B personality disorders [ 38 , 39 ], and ASD.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective review concluded that depressed patient with psychotic delusion can be five times more likely to commit suicide than a nondelusional one [71]. Overall, delusional depression has a poorer prognosis than nonpsychotic depression [72], and is less responsive to antidepressants [73].…”
Section: Evidence Base For Ect Effectiveness Efficacy and Tolerabilitymentioning
confidence: 99%